Pengaruh Penerapan Sistem Bagi Hasil Syariah terhadap Kinerja Koperasi Berbasis Balanced Scorecard dengan Komitmen Organisasi sebagai Variabel Moderasi - Zulkarnaini, Zulkarnaini; Lakharis Inuzula; Zulfikar Zulfikar; Kheriah Kheriah; Julia Alfianti; Mariana Mariana (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2025)
This study investigates the implementation of cooperative performance measurement using the Balanced Scorecard (BSC) framework, with a specific focus on the influence of the Sharia-based profit-sharing system and the moderating role of organizational commitment. Drawing on a sample of 33 Sharia-based cooperatives in Lhokseumawe, the study employs multiple linear regression and Moderated Regression Analysis (MRA) to test the proposed model. The findings reveal a significant positive impact of the Sharia-based profit-sharing system on BSC-based performance (path coefficient = 0.573; p < 0.001), as well as a strong influence of organizational commitment (path coefficient = 0.568; p < 0.001). Notably, the interaction effect between profit-sharing and organizational commitment is also significant (path coefficient = 0.107; p = 0.004), indicating that high organizational commitment enhances the effectiveness of Sharia-compliant systems in driving BSC performance. This research contributes to the limited body of literature that integrates Islamic financial principles with strategic performance frameworks, offering a novel perspective on how religious-based financial systems can be synergized with modern management tools to improve cooperative performance.